Renegade lawyer : the life of J.L. Cohen - MacDowell, Laurel Sefton, 1947- (Osgoode Society for Canadian Legal History Ser., 2001)
"J. L. Cohen, one of the first specialists in labour law and an architect of the Canadian industrial relations system, was a formidable advocate in the 1930s and 1940s on behalf of working people. In representing the less powerful and seeking to reform society and protect civil liberties, he was a 'radical lawyer' in the tradition of the great American counsel Clarence Darrow and contemporary Canadian advocate Thomas Berger. Cohen was also among a group of 'labour intellectuals' in Canada, similar to those in the United States who supported Roosevelt's New Deal. He wrote Collective Bargaining in Canada, served on the National War Labour Board, and advised the Ontario government about policy issues such as mothers' allowances, unemployment insurance legislation, and labour law." "In this biography, Laurel Sefton MacDowell presents a thorough and insightful account of a brilliant but complex public figure. Cohen's commitment to the labour movement resulted in part from his background as a Marxist and a Jewish immigrant, and was deepened by his experience of the Depression. His was an unusual perspective for a middle-class professional, and his ethnic origins and political views subjected him to discrimination. Though respected professionally, he made enemies. At the end of the war, Cohen was convicted of a criminal charge; he was disbarred but later reinstated, and died suddenly in 1950 at the age of fifty-three. Though he rose to the top of his profession, he had a difficult, complicated private life, which contributed to his personal disgrace and professional downfall. His obituary in the Globe and Mail described him as a dynamic, sharp-witted man who rose from humble beginnings to become the most influential labour lawyer in Canada, and it concluded with what may be a fitting epitaph, 'He championed all the wrong people in all the right things.'"--Jacket